(untitled) (Analysis in Theory and Applications, 2017)
Let f be an H−periodic Hölder continuous function of two real variables. The error ||f −N_n(p;f)|| is estimated in the uniform norm and in the Hölder norm, where p=(p_k)^∞_k=0 is a nonincreasing sequence of positive numbers and N_n(p; f) is the nth Nörlund mean of hexagonal Fourier series of f with respect to p=(p_k)^∞_k=0.